Systemic inhibition of BMP1-3 decreases progression of CCl4-induced liver fibrosis in rats. (2nd November 2017) - Grgurevic, Lovorka; Erjavec, Igor; Grgurevic, Ivica; Dumic-Cule, Ivo; Brkljacic, Jelena; Verbanac, Donatella; Matijasic, Mario; Paljetak, Hana Cipcic; Novak, Rudjer; Plecko, Mihovil; Bubic-Spoljar, Jadranka; Rogic, Dunja; et al.
Abstract: Liver fibrosis is a progressive pathological process resulting in an accumulation of excess extracellular matrix proteins. We discovered that bone morphogenetic protein 1-3 (BMP1-3), an isoform of the metalloproteinase Bmp1 gene, circulates in the plasma of healthy volunteers and its neutralization decreases the progression of chronic kidney disease in 5/6 nephrectomized rats. Here, we investigated the potential role of BMP1-3 in a chronic liver disease. Rats with carbon tetrachloride (CCl4 )-induced liver fibrosis were treated with monoclonal anti-BMP1-3 antibodies. Treatment with anti-BMP1-3 antibodies dose-dependently lowered the amount of collagen type I, downregulated the expression of Tgfb1, Itgb6, Col1a1, and Acta2 and upregulated the expression of Ctgf, Itgb1, and Dcn . Mehanistically, BMP1-3 inhibition decreased the plasma levels of transforming growth factor beta 1(TGFβ1) by prevention of its activation and lowered the prodecorin production further suppressing the TGFβ1 profibrotic effect. Our results suggest that BMP1-3 inhibitors have significant potential for decreasing the progression of fibrosis in liver cirrhosis.